2014
DOI: 10.1126/scisignal.2005070
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Poly(ADP-Ribose) Polymerase and the c-Myb–Regulated DNA Damage Response Pathway in Castration-Resistant Prostate Cancer

Abstract: Androgen deprivation is the standard systemic treatment for advanced prostate cancer (PCa), but most patients ultimately develop castration-resistance. We show here that MYB is transcriptionally activated by androgen deprivation or impairment of androgen receptor (AR) signaling. MYB gene silencing significantly inhibited PCa growth in vitro and in vivo. Microarray data revealed that c-Myb shares a substantial subset of DNA damage response (DDR) target genes with AR, suggesting that c-Myb may replace AR for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
95
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 37 publications
4
95
1
Order By: Relevance
“…Li et al recently found that ENZ increased expression of the proto-oncogene c-MYB, a transcription factor that has been shown to be upregulated in multiple malignancies [7]. The results of this study showed that c-Myb increases growth and metastatic potential of both AR-positive and AR-negative PCa cells [7].…”
Section: New Targets For Resistant Prostate Cancer Timothy C Thompsosupporting
confidence: 58%
See 4 more Smart Citations
“…Li et al recently found that ENZ increased expression of the proto-oncogene c-MYB, a transcription factor that has been shown to be upregulated in multiple malignancies [7]. The results of this study showed that c-Myb increases growth and metastatic potential of both AR-positive and AR-negative PCa cells [7].…”
Section: New Targets For Resistant Prostate Cancer Timothy C Thompsosupporting
confidence: 58%
“…The results of this study showed that c-Myb increases growth and metastatic potential of both AR-positive and AR-negative PCa cells [7]. c-Myb expression was increased in AR-positive, androgenindependent PCa cells compared with PCa cells that were dependent on androgens for growth.…”
Section: New Targets For Resistant Prostate Cancer Timothy C Thompsomentioning
confidence: 62%
See 3 more Smart Citations